UJI KRITERIA INSTRUMEN PENILAIAN HASIL BELAJAR KIMIA (Universitas Negeri Semarang, 2014)
This research was conducted with descriptive method to determine the results of assessment criteria for learning outcomes instrument in chemistry subject of class XI. The test include the analysis of the validity, difficulty index, level of matter, distractor effectiveness and reliability of the odd semester final examination in the academic year 2013/2014 chemistry subjects at a Public Senior High School of Ambarawa and a Public Islamic Senior High School of Suruh. Form of matter that is analyzed is multiple choice, with total 40 items. Based on the test results in Public Senior High School of Ambarawa, it is known that 27 items valid, by about C1/know up to C3/apply level. There are 3 tems was difficult, 12 items medium, and 25 items easy. Of the total 160 existing distractor items, 89 items classified distractor effective. Instruments classified as reliable because it has a reliability coefficient of 0.70. While the test results in Public Islamic Senior High School of Suruh, 28 items were classified as valid items by about C1/know up to C4/analyze level. There are 10 items was medium and 30 items easy. Effective distractor was 91 items. Instruments classified as reliable because it has a reliability coefficient of 0.81.Keywords: Assessment, Criteria, Instrument